(untitled) (Revista Brasileira Multidisciplinar, 2025)
The pandemic caused by SARS-CoV-2 has led to several changes in society’s behavioral patterns. Social isolation and the pandemic, in general, have been important factors in the development of various psychiatric disorders in Brazil and around the world, such as anxiety disorders and depression, as well as in the increase in prescriptions for antidepressants and anxiolytics. This study analyzed the trend in prescriptions for antidepressants and anxiolytics in 2020. A cross-sectional, retrospective and quantitative analysis was carried out, using prescriptions retained in units of a private pharmacy chain, from January 1, 2020 to December 31, 2020, assessing the trend in prescriptions during the initial year of the pandemic. A total of 1072 prescriptions were analyzed, showing an increase in prescriptions for antidepressants and anxiolytics. There was a gender disparity between prescriptions for men and women, with women being more prevalent. There was a predominance of prescriptions made by general practitioners, indicating a shortage of specialists in the countryside. Finally, there is a need for public policies that enable greater monitoring of the dispensing of psychotropic drugs, as well as making more specialist doctors available in the interior of Brazil.